A companion to Apollonius Rhodius - Papanghelis, Theodore D.; Rengakos, Antonios (Mnemosyne, bibliotheca classica Batava. Supplementum ;, 2001)
This collection of essays, on the author of the "Argonautica", covers a wide range of issues from the history of the text and the problems of the poet's biography through questions of style, literary technique and intertextual relations to the epic's library and cultural reception.